Quels curricula d’éducation au politique dans les questions environnementales et de développement ? - Angela Barthes (Éducation et Socialisation)
We propose a definition of what an education to politics can be, then what it implies in concrete terms to intentionally set up curricula of an education to politics between decoding of epistemologies of politically situated knowledge, multi-referentiality of social relations, problematization and decoding of power and injustice relations. It repositions a history of environmental and development education in a political education perspective to show the role of institutional, activist and scholarly spheres in the successive phases and currents of environmental, sustainable development and anthropocene education. We also show a recent paradigm shift following two decades of anomie from strongly behaviorist-based sustainable development education to anthropocene education and other meta-narratives that offer more potential for political socialization.